Key Competencies of Filipino Teachers for Inclusive Education: Insights from a Delphi Study - Princess Zarla J. Raguindin; Li Yan Ping (SAGE Open)
This study explores the pedagogical competencies that Filipino in-service teachers need to possess to foster the implementation of inclusive education in the general education setting. Through a Delphi method, the research engaged 12 experts to achieve consensus on key competencies important for teachers to have to implement inclusion. The study employed three iterative rounds, ensuring a robust analysis of the identified technical skills, specific knowledge, and inclusionary attitudes required to implement inclusion. The findings revealed six critical domains, with 52 indicators, of the competency standards important in implementing inclusive education: understanding of inclusion, high regard for inclusion, pedagogy for inclusive classrooms, personal and professional development, and ethical and human rights issues. The areas highlighted by the experts contribute to the discourse on inclusive education through a framework that supports teachers in fostering equitable and inclusive learning environments. The framework also serves as a practical guide for teacher training and development. Equipping educators to create inclusive and equitable learning environments ensures the engagement, participation, and academic success of all learners. Ramifications for educational policies aligned with global goals of inclusion while addressing the unique context of the Philippines are also underscored. By identifying the gaps in teacher education and offering a structured approach, this study contributes to the enhancement of educational practice and teacher training.